Genetic diversity in quality protein maize QPM inbreed lines - Kumar, Ramesh; Dubey, RB; Ameta, KD; Verma, Rajani (Bangladesh Journal of Botany, 2020)
The experimental material consisting of 18 lines and four standard checks were raised in RBD in three replications. Significant differences between the test entries were observed for all the traits. Twenty-two genotypes were grouped into VII clusters on the basis of observed distance among genotypes within a cluster as compared to genotypes in another cluster. Cluster III contains maximum number (seven) of genotypes. Cluster I had highest grain yield per plant, 100-grain weight, harvest index and tryptophan content while cluster VII had lowest anthesis silking interval and highest oil and lysine content and cluster V had maximum starch content. The better performing genotypes from clusters I, II and III were identified for all the traits. Therefore, F1 derived from such diverse crosses is expected to show high yield.